INFLUENCE OF LONGITUDINAL FORCES FOR DETERMININGTHE FREQUENCY OF FREE OSCILLATIONS DISCRETE DYNAMIC SYSTEMS - Shkurupiy, A. A.; Mytrofanov, P. B. (Academic journal Industrial Machine Building Civil Engineering, 2017)
In the research flat and spatial rod system as a part of many engineering and technical structures were considered. A new construction with a simultaneous increase quality of their design requires finding new ways to improve dynamic analysis and calculation of complex rod systems. It was analyzed, that longitudinal forces consideration when determining discrete dynamical systems free oscillations frequency together with use of modern computer hardware and software systems allows to reduce time for such calculations, and use the innovative schemes and methods that were previously inaccessible through large amounts of computing. The problem of road systems free oscillations frequencies with finite number of freedom degrees in bending with considering of longitudinal forces was considered. The examples of quantitative assessment influence of longitudinal forces on the frequencies of free oscillations were shown.
Keywords: free oscillations; , longitudinal force; frequency; dynamic system; load